2014
DOI: 10.1039/c4cp00667d
|View full text |Cite
|
Sign up to set email alerts
|

The role of water co-adsorption on the modification of ZnO nanowires using acetic acid

Abstract: Density functional theory (DFT) and Car-Parinello molecular dynamic simulations were employed to investigate the interaction of acetic acid with non-polar facets of ultra-thin ZnO nanowires. We consider both a dry and a water environment as well as different molecule coverages for the hydrated system. Our calculations reveal that the fully-covered nanowire is energetically favored in the aqueous environment at room temperature. We also identified a minor influence of liquid water on the denticity of the ligand… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 42 publications
1
5
0
Order By: Relevance
“…This leads to one ligand per surface unit cell. As we have shown in previous studies, 27,29,58 this surface coverage is the thermodynamically most stable one.…”
Section: A Surfacesmentioning
confidence: 58%
“…This leads to one ligand per surface unit cell. As we have shown in previous studies, 27,29,58 this surface coverage is the thermodynamically most stable one.…”
Section: A Surfacesmentioning
confidence: 58%
“…The results showed that the process of adsorption of acetic acid is exothermic. The higher absolute value of adsorption energy indicated that the acetic acid can be stable adsorption . The contact of active metal and acetic acid was enhanced, resulting in increase of carbon conversion and hydrogen yield and so on.…”
Section: Resultsmentioning
confidence: 99%
“…The higher absolute value of adsorption energy indicated that the acetic acid can be stable adsorption. 59 The contact of active metal and acetic acid was enhanced, resulting in increase of carbon conversion and hydrogen yield and so on. On the other hand, the adsorption of steam on the perovskite surface was also calculated, as shown in Figure 9.…”
Section: Dft Calculationmentioning
confidence: 99%
“…[47][48][49] We hypothesized that adding water to the mobile phase increases the recovery ratios of these compounds because water competitively coordinates to ZnO NWs and has a high dielectric constant. 50,51 Fig. 2a shows the recovery ratios of monosubstituted benzenes with acidic functional groups in the mobile phase containing water.…”
Section: Retention Behaviors Of Monosubstituted Benzenes On the Zno-n...mentioning
confidence: 99%